Effect of faecal sludge on cabbage production - Islam, Md Shafiqul; Hasan, Monjur (International Journal of Agricultural Research, Innovation and Technology, 2017)
2.7 billion people worldwide rely on onsite sanitation and it is a big problem in developing countries. Faecal sludge is a good source of micro/macronutrients of plant besides its richness in organic matter. Two consecutive field experiments was conducted in BRAC Agricultural Research and Development Centre, Gazipur during Rabi 2015-16 and rabi 2016-17 aimed to determine the effect of faecal sludge on crop production and how much dosage need for maximum yield. Cabbage was the test crop. It was observed that harvesting time was significantly shortened and 25.51% curd weight and 26.55% yield was increase with addition of faecal and chemical fertilizer. No significant differences were found on the dosage of faecal on head formation and head diameter. In the addition of full dosage of faecal with chemical fertilizer, 41.04% and 8.61% curd weight increase than only faecal and chemical fertilizer. Application of full dosage of faecal with full dosages of chemical increases yield 7.28%, 10.66%, 6.88% and 38.75 % than application of half faecal, three-fourth faecal, only chemical fertilizer and only faecal. So addition of full dosage of faecal with chemical fertilizer gives the highest yield on crop. In Bangladesh, faecal might be recycled into agricultural soils as a supplement to commercial fertilizer and thereby enrich the general fertility of the soils and increase crop production. Int. J. Agril. Res. Innov. & Tech. 7 (1): 43-45, June, 2017